CSIG-17. PRMT5 INHIBITION SENSITIZES GLIOBLASTOMA MODELS TO TRAMETINIB TREATMENT. (9th November 2020) - Otani, Yoshihiro; Namagiri, Sriya; Thammegowda, Shilpa; Sur, Hannah; Chowdhury, Ashis; Lewis, Cole; Shimizu, Toshihiko; Lee, Tae Jin; Maric, Dragan; Yoo, Ji Young; Heiss, John; Kaur, Balveen; et al.
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most common malignant primary brain tumor. With limited effective therapeutic strategies, prognosis for GBM is very poor. Our previous study shows that the expression of Protein Arginine Methyltransferase 5 (PRMT5) is upregulated in GBM; its inhibition promotes anti-GBM effect through apoptosis and senescence of mature and immature tumor cells, respectively. In GBM, RAS-RAF- MEK-ERK signaling is aberrantly activated and promotes tumor growth. Therefore, MEK inhibitors, including trametinib are currently under investigation for GBM therapy. In this study, we tested whether inhibition of PRMT5 can enhance the anti-tumor efficacy of trametinib in GBM. METHODS: Patient-derived primary GBM neurospheres (GBMNS) with transient PRMT5 knockdown were treated with trametinib and cell viability, proliferation, cell cycle progression, and western blot analysis were conducted. In vivo, PRMT5-intact and -depleted GBMNS were intracranially implanted in NSG mice and treated with trametinib by daily oral gavage, and tumor progression and mice survival rate were analyzed by MRI and Kaplan-Meier survival curve, respectively. RESULTS: Trametinib treatment upregulated the expression of PRMT5 in GBMNS. Depletion of PRMT5 increased the cytotoxic effect of trametinib in GBMNS. In concurrence with the trametinib-induced PRMT5 upregulation, trametinib treatment increased the activity of AKT that was blocked with PRMT5 knockdown. In vivo, PRMT5-depletion extended the survival of the tumor bearing mice that further increased in combination with trametinib treatment. Interestingly, trametinib treatment alone had no survival benefit. CONCLUSION: Trametinib treatment induces PRMT5 expression. Depletion of trametinib-induced PRMT5 expression sensitizes GBMNS for trametinib by inhibiting AKT activity.